PROPRIEDADES ÓPTICAS DE VIDROS ALUMINOSILICATOS DOPADOS COM ÍONS DE CE3+, EU3+, TI3+ PARA GERAÇÃO DE LUZ INTELIGENTE SINTONIZÁVEL - Amorin, Paula; Andrade, Luis Humberto; Lima, Sandro; Finoto, Simone Finoto; Yamamoto, Claudio (ANAIS DO ENIC, 2018)
-